Identifikasi Kualitas Udara Ambien dan Tingkat Kebisingan di Wilayah Pantai Siring Pagatan, Kalimantan Selatan - Sari, Gina Lova; Nurkhaerani, Fatma; Adzillah, Wilma Nurrul (Al-Ard: Jurnal Teknik Lingkungan, 2024)
Tourism is an activity that is of concern to Indonesian people, especially beach tourism, such as at Siring Pagatan Beach, Tanah Bumbu Regency, South Kalimantan. This tourism is dominated by culinary, religious, and transportation activities which have an impact on increasing the creative economy of the community. However, these activities also have the potential to cause environmental and health problems due to gas emissions and noise. To avoid the impact, it is necessary to identify and analyze the ambient air quality and noise levels at Siring Pagatan Beach. This study is essential, considering the vast potential and development of tourism activities in the research area, which is close to residential areas. In the study area, the ambient air quality, in terms of total particulates; PM10; PM2.5; NO2; SO2; and CO were measured using Indonesian National Standard No. 19-7119.6-2005 in four locations, while noise levels were carried out in 2 two locations according to Indonesian National Standard No. 8427-2017 in the study area. The results showed that the total amount of total particulates; PM10; PM2.5; NO2; SO2; and CO are 60.23-90.15; 25.07-70.02; 14.66-48.01; 0.95-5.31; 14.46-26.48; and 1917.14-1382.86 g/m3. Meanwhile, the noise obtained was 52.00-52.20 dBA. The value of these environmental components is below the threshold value in Indonesia. However, with ongoing tourism infrastructure development activities, there is the potential for increased pollutant concentrations and noise levels at the research location, which may impact the surrounding community in the long term.